2020
DOI: 10.1111/joca.12338
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in holding a retirement saving motive: A decomposition analysis

Abstract: Establishing a retirement goal facilitates one's long‐term financial planning behavior. Yet, the portion of U.S. households who achieve this goal is relatively small. Further, the percentage is much lower among racial and ethnic minorities. This study investigates racial/ethnic disparities in motives for holding a retirement savings and contributing factors to explain the gaps. Results from the 2016 Survey of Consumer Finances (SCF) indicate that White respondents were more likely to hold a retirement saving m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The results show that the financial literacy level affects the saving behavior of this group, thus coinciding with the international evidence that exists regarding the relationship between these two variables [26][27][28][29][30][31] and that higher financial literacy levels increase people's savings rate.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results show that the financial literacy level affects the saving behavior of this group, thus coinciding with the international evidence that exists regarding the relationship between these two variables [26][27][28][29][30][31] and that higher financial literacy levels increase people's savings rate.…”
Section: Discussionsupporting
confidence: 82%
“…There is sufficient evidence in the literature that financial literacy effectively increases the savings rate [26][27][28][29][30][31]. Struckell et al [32] refer that it is necessary for both self-employed workers and employees to be financially literate since it is advisable for them to acquire skills and knowledge that allow them to prepare for budget planning, business plans and evaluate financial challenges they face within the labor market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, disattenuated for imperfect reliability (internal consistency reliability = 0.45), the true score standardized beta‐weight would correspond to −0.12, an effect 50% large than the originally reported effect. As a final example, in a study that predicted retirement savings motive with the Big Three, Kim et al (2020) reported statistically significant odds ratios of 1.13. Thus, higher levels of financial literacy were associated with a greater likely of having a retirement savings motive.…”
Section: Implications For Financial Literacy Researchmentioning
confidence: 99%
“…Despite the relatively large number of financial literacy tests available to researchers, many studies continue to rely on only the Big Three or the Big Five financial literacy tests (e.g., Davidoff et al, 2017; Goda et al, 2019; Kim et al, 2020). Arguably, one reason researchers select financial literacy tests with so few questions is precedent: many publications select previously used scales, perhaps because no one has specifically questioned it.…”
Section: Introductionmentioning
confidence: 99%
“…While everyone needs to have retirement savings in order to have financial security in their old age, BIPOC households do not have enough. In this volume, Kim, Cho, and Devaney (2021) examine motives for saving for Black and white households and find that Black households are significantly less likely than White households to save for the purpose of retirement relative to other shorter‐term goals, even after controlling for socioeconomic characteristics such as homeownership, objective financial knowledge, planning horizon, and age. Black savers, in particular, focus first on homeownership before retirement.…”
Section: Action For Racial Justicementioning
confidence: 99%